PbS and PbS/CdS quantum dots: Synthesized by photochemical approach, structural, linear and nonlinear response properties, and optical limiting. Issue 4 (28th February 2020) - Molaei, Mehdi; Karimipour, Masoud; Abbasi, Samaneh; Khanzadeh, Mohammad; Dehghanipour, Masoud
Abstract: Abstract : In this work, PbS and PbS/CdS core–shell quantum dots (QDs) were synthesized by a new photochemical approach. Prepared QDs were characterized by means of x-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), energy dispersive x-ray analysis (EDAX), UV–Vis, and Z-scan analyses. Synthesized QDs were in a cubic phase with a spherical morphology, and the crystallite sizes are estimated using the strain–size method. A uniform shift of Bragg diffraction peaks and quenching (200) Bragg plane are interpreted as the growth of the CdS shell. Linear optical properties were investigated using Urbach analysis and Tauc formula. It was found that the density of states of QD conduction and valence bands are three dimensional. The estimated sizes of PbS QDs and PbS/CdS using exciton absorption peaks at room temperature are 1.8 and 2.7 nm, respectively, which are in good agreement with the strain–size plot analysis. The growth of the CdS shell resulted in a considerable decrease in the nonlinearity refractive index and a significant increase in the nonlinear absorption.